Ultrasound elastography applications (Community Based Medical Journal, 2013)
Ultrasound elastography (EUS) is a method to assess the mechanical properties of tissue, by applying stress and detecting tissue displacement using ultrasound. There are several EUS techniques used in clinical practice; strain (compression) EUS is the most common technique that allows real-time visualisation of the elastographic map on the screen. There is increasing evidence that EUS can be used to measure the mechanical properties of musculoskeletal tissue in clinical practice, with the future potential for early diagnosis to both guide and monitor therapy. This review describes the various EUS techniques available for clinical use, presents the published evidence on musculoskeletal applications of EUS and discusses the technical issues, limitations and future perspectives of this method in the assessment of the musculoskeletal system. Ultrasound elastography (EUS) is a recently developed ultrasound-based method, which allows the qualitative visual or quantitative measurements of the mechanical properties of tissue 1. The technique was first introduced in vitro in the early 1990s, and subsequently evolved into a real-time tool for in vivo imaging of the distribution of tissue strain and elastic modulus 2. EUS provides information on tissue stiffness, which complements and is independent from the acoustic impedance and vascular flow information provided by B-mode and Doppler imaging, thus opening a new dimension in diagnostic imaging 3 . EUS is based upon the general principle that stress applied to tissue causes changes within it, which depend on the elastic properties of tissue 3. Over the years of research on elasticity, there have been several approaches of EUS, resulting in different methods, depending on the way of tissue stress application and the used method to detect and construct an image of tissue displacement 3. Strain (compression) EUS is the commonest technique that allows real-time visualisation of the image on the screen, and it has been successfully employed to detect and characterise lesions in a variety of tissues and organs 5 . Disease in the musculoskeletal system results in alterations to its biomechanical properties. Although EUS techniques have been extensively employed for in vitro research of muscle and tendon biomechanics since the early 1990s 6 , the recent introduction of EUS into commercially available ultrasound systems has driven research activity towards potential clinical applications of this novel method in the musculoskeletal system 7.  This review aims to describe the various EUS techniques available for clinical use, present the available published evidence on musculoskeletal applications of EUS, and finally discuss the limitations and future perspectives of this technique for assessing the musculoskeletal system. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14191 Community Based Medical Journal Vol.2(1) 2013 76-85